Data rate maximization by adaptive thresholding RF power management under renewable energy - Weiguo Tang; Lei Wang (2010 IEEE International Conference on Computer Design, 2010)
A new adaptive thresholding power management (ATPM) scheme is proposed to maximize the data rate of RF circuits in distributed embedded systems powered by renewable energy. Considering time-varying fading channels and statistical energy harvesting processes, we propose to turn on RF circuits only when the channel gain is higher than a threshold, and adjust the RF power according to the energy availability to improve the overall data rate. Exploiting the fact that the optimal threshold is a function of variable renewable energy subject to environmental changes, we adaptively adjust the threshold in accordance with renewable energy to improve energy efficiency. Simulation results based on solar energy indicate that the proposed ATPM scheme increases the average data rate by up to 60% compared with the scheme without channel gain thresholding, and achieves over 5X improvement in data rate over the constant power scheme with the same RF power consumption.